Iowa Corn and Soybean Producers' Use of Communication Channels - Melea A. R. Licht; Robert A. Martin (Journal of Applied Communications, 2006)
The purpose of this study was to determine the agricultural information preferences of corn and soybean producers in Iowa and the implications for agricultural Extension education. The specific objective of this report was to identify how Iowa producers use communication channels to obtain agricultural information. The results will help agricultural Extension educators and communicators make informed decisions regarding program delivery. The study collected data from corn and soybean producers in five focus groups held throughout Iowa. Focus group data were collected as audiotapes and transcriptions. Analysis was performed through theme coding and qualitative data charts. Study findings revealed that a) producers used a variety of communication channels to gather agricultural information, b) producers primarily used radio and consultations for gathering agricultural information, c) producers used mass media channels for general information and interpersonal communication channels for specific and applicable information, and d) producers looked to Extension for assistance in evaluating information gathered from other sources.